Paradojas del escepticismo. Sexto Empirico en los límites de la filosofía (Argos, 2024)
In this article three paradoxes of the thought of Sextus Empiricus are presented: the ontological paradox, because on the one hand it proposes to rely only on appearances, but it is impossible to avoid referring to external things; the linguistic paradox, according to which it is not possible to affirm anything, but there is no closure of language and argument for the skeptic; and the ethical paradox, which invites to disbelieve the existence of the good, but invites us to act according to some practical criterion. After reviewing them, the paper proposes an interpretation of sextian skepticism that gives meaning to paradoxes without commiting contradictions.
Keywords: Scepticism; Sextus Empiricus; paradox; ontology; natural good